Size dependence on shear fatigue and fracture behavior of ball grid array structure Cu/Sn–3.0Ag–0.5Cu/Cu solder joints under current stressing - Wang, Bo; Li, Wangyun; Pan, Kailin; Huang, Wei; Gong, Yubing (Frontiers in Materials, 2024)
The shear fatigue performance and fracture behavior of microscale ball grid array (BGA) structure Cu/Sn-3.0Ag-0.5Cu/Cu solder joints with different heights (500 μm, 300 μm, and 100 μm) with increasing current density (from 6000 to 11000 A/cm2) were investigated systematically. The results reveal that the fatigue life of solder joints decreases with increasing current density, while increasing with decreasing the height of solder joints. The location of fatigue fracture shifts from solder matrix to the interface between solder and intermetallic compound (IMC) layer for those with heights of 500 μm and 300 μm with increasing current density, in which the interfacial fracture is triggered by current crowding at the groove of the IMC layer and driven by mismatch strain at the solder/IMC layer interface; while, the fatigue fracture all occurs in the solder matrix for solder joints with a height of 100 μm. Moreover, the fracture in solder matrix of solder joints with heights of 500 μm and 300 μm exhibits an arc-shape fracture path, while a linear path for those with a height of 100 μm. These fracture paths are consistent with the concentration distribution region of plastic strain energy in solder joints.